Iron-based metal-organic framework: Synthesis, structure and current technologies for water reclamation with deep insight into framework integrity. (December 2021) - Joseph, Jessy; Iftekhar, Sidra; Srivastava, Varsha; Fallah, Zari; Zare, Ehsan Nazarzadeh; Sillanpää, Mika
Abstract: Water is a supreme requirement for the existence of life, the contamination from the point and non-point sources are creating a great threat to the water ecosystem. Advance tools and techniques are required to restore the water quality and metal-organic framework (MOFs) with a tunable porous structure, striking physical and chemical properties are an excellent candidate for it. Fe-based MOFs, which developed rapidly in recent years, are foreseen as most promising to overcome the disadvantages of traditional water depolluting practices. Fe-MOFs with low toxicity and preferable stability possess excellent performance potential for almost all water remedying techniques in contrast to other MOF structures, especially visible light photocatalysis, Fenton, and Fenton-like heterogeneous catalysis. Fe-MOFs become essential tool for water treatment due to their high catalytic activity, abundant active site and pollutant-specific adsorption. However, the structural degradation under external chemical, photolytic, mechanical, and thermal stimuli is impeding Fe-MOFs from further improvement in activity and their commercialization. Understanding the shortcomings of structural integrity is crucial for large-scale synthesis and commercial implementation of Fe-MOFs-based water treatment techniques. Herein we summarize the synthesis, structure and recent advancements in water remediation methods using Fe-MOFs in particular more attention is paid for adsorption, heterogeneous catalysis and photocatalysis with clear insight into the mechanisms involved. For ease of analysis, the pollutants have been classified into two major classes; inorganic pollutants and organic pollutants. In this review, we present for the first time a detailed insight into the challenges in employing Fe-MOFs for water remediation due to structural instability. Graphical abstract: Image 1 Highlights: Strategies of designing and synthesis of Fe-MOFs are reviewed. Fe-MOFs utilization in organic pollutant removal is reviewed. Mechanisms involved in the Fe-MOFs based water treatment are discussed. The structural integrity of Fe-MOFs, challenges and possible research perspectives are provided.